"Strange" But Not Queer: Intellectual Disability and Participation in the Body of Christ. (3rd April 2022) - Micale, Calli
Abstract: This essay examines Brian Brock's use of imagery and symbols in Wondrously Wounded to explain reception of the Spirit's gifts. By recovering the symbol of wonder, Brock intervenes in discussions among disability theologians about participation in Christ's body. Above all, he avoids normative discursive forms that work to subordinate those marked disabled. Recent directions in queer theology, however, show that images of wounding and assault reinstate logics of opposition, subordination, and subjection. Drawing from Linn Tonstad and Ashon Crawley, this essay modifies Brock's proposal by suggesting that images of abundance and excess better illuminate the reconfiguration of community in Christ.